Resolution of α-methylserine dervatives via lipase mediated acetylation - Koźniewski, Bartłomiej; Kamińska, Janina (Wydawnictwo Politechniki Łódzkiej, 2011)
(±)-N-Benzoyl-α-methylserine ethyl ester and (±)-4- hydroxymethyl-4-methyl-2-phenyl-1,3-oxazol-5(4H)-one were synthesized and used as substrates for enzyme catalyzed kinetic resolution in organic solvents. Several lipases active for O-acetylation of both compounds were found. The most active enzymes were screened for influence of solvent, acetyl donor type, its concentration, biocatalyst quantity and reaction temperature on resolution rate and enantioselectivity ratio E. For acetylation of (±)-N-benzoyl-α-methylserine ethyl ester with isopropenyl acetate in the presence of Novozym ® 435 the highest enantioselectivity E = 35 was found, yielding at 54% conversion (S)-N-Benzoyl-α-methylserine ethyl ester with 94% ee and (R)-O-acetyl-N-benzoyl-α-methylserine ethyl ester with 82% ee.